The temporo-mandibular joint: Reconstruction of the condyle post-ablation - Rhodri Davies; Luke Cascarini (Journal of Oral Biology and Craniofacial Research, 2022)
Ablative surgery of the mandibular condyle poses a unique reconstructive challenge for many reasons. The condyle and it's relationship to the TMJ is a unique, complex, functional and aesthetically relevant piece of human anatomy. Resection may be required for both malignant and benign pathologies; each posing a differing set of surgical variables. Particularly in neoplastic processes, there must remain a certain degree of peri-operative flexibility with regards to the extent of the resection, and forethought to the requirement for post-operative radiotherapy; both of which further complicate choice of reconstructive option and surgical or prosthetic planning. The cases involved can often concern paediatric patients, and an additional aspect to be considered is that of growth potential.In this piece, we will discuss the indications for ablation and the techniques involved. We will elaborate on the reconstructive challenges specific to reconstructing the condyle in post-ablative cases. We will then describe and analyse the established reconstructive techniques; aiming to provide a balanced view on the advantages and disadvantages. Our focus will include autologous options such as vascularised and non-vascularised free tissue transfer, and the non-autologous options of custom and stock implants. We will also touch on distraction osteogenesis and ramus osteotomies. Lastly we will look to the future and consider possible innovative techniques which may become available to the surgeon.